Aging and consumer decision making - Carpenter, Stephanie M. (2011)
Research on consumer decision making and aging is especially important for fostering a better understanding of ways to maintain consumer satisfaction and high decision quality across the life span. We provide a review of extant research on the effects of normal aging on cognition and decision processes and how these age-related processes are influenced by task environment, meaningfulness of the task, and consumer expertise. We consider how research centered on these topics generates insights about changes in consumption decisions that occur with aging and identify a number of gaps and directions for future research.